Investigation on Power System Optimization and Voltage Stability Related Problems - A., Arunagiri (2005)
The Optimal Power Flow(OPF) problem was first defined in the early sixties. In this thesis, a method is proposed to solve the OPF problem considering multiple objectives of generation cost minimization, transmission loss minimization and voltage stability margin maximization. The proposed method employs Successive Fuzzy LP (SFLP) technique. The system voltage stability margin is quantified using singular values of the system load flow Jacobian. The voltage stability margin is maximized by maximizing few least singular values of the load flow Jacobian. Constraints on control and dependent variables are considered.